(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
The aim of the paper is to analyse and compare graphic elements of visual communication on selected journal covers. The research was conducted using the covers of the journals Zarez, Vijenac and Kolo published from 1999 to 2011. The journal sample was selected based on the availability of periodicals, their topic and their cultural and social relevance. The research showed that visual communication on journal covers varies depending on the identity of the journal. Images are the key element in creating the message on the cover, they determine the way a journal communicates, giving it style, tone, and depth. Although thematically very similar, the journals we compared speak a different visual language. The main characteristic of Zarez is the daring and ironic visual communication that criticizes social events. In Vijenac, and in Kolo in particular, a more passive method of communication is used, which merely reflects the society and culture in which it is situated and about which it testifies. Focused on comments about general social and cultural events, without any real involvement, Kolo lacks the key element of visual communication that intrigues and directs readers’ attention to the journal.